The effects of soy products and preparations on health issues of menopausal women in the light of randomized clinical studies (part 1) - Kanadys, Wiesław M. (Menopause Review/Przegląd Menopauzalny, 2005)
Recent published large trials of HERS, WHI, and Million Women Study showed increased risk of cholelithiasis, venous thromboembolic events, coronary events, stroke, breast cancer besides known benefits of postmenopausal hormone therapy. Putting special emphasis on health hazard associating with long term therapy, as well as fear of neoplasms, especially breast cancer, fear of weight gain, problem of irregular bleeding during therapy caused significant reduce of percentage of sex hormones users. It found expression in increased concern of complementary and alternative therapy. Epidemiologic data indicated, that women ingesting high amounts of soy products had less cardiovascular disease, breast and uterine cancer and menopausal symptoms. Author presents articles about the effect of soy preparations (soy protein and/or isoflavones extracts) on health issues of menopause, leaning on randomized clinical studies. However data are often conflicting and difficult to analyze because of variations in studied populations, inclusion criteria, soy products used, duration of study. Data support a benefit of soy and isoflavones on hot flash frequency and severity, but only a small part of this benefit is due to soy preparations per se because in these studies the placebo group also reports a large benefit. Use of soy and/or isoflawones does not seem to affect on atrophic vaginits and on endometrium. At present there is lack of randomized, controlled trials examining the effects of soy and isoflavones on breast glandular tissue. Caution should be exercised with initiating soy therapy among women with increased risk of breast cancer.